2017
DOI: 10.1016/j.jbankfin.2015.04.020
|View full text |Cite
|
Sign up to set email alerts
|

The stability of short-term interest rates pass-through in the euro area during the financial market and sovereign debt crises

Abstract: Papier disponible en WP sous la référence hal-01511667International audienceWe analyse the dynamics of the pass-through of banks’ marginal cost to bank lending rates over the 2008 crisis and the euro area sovereign debt crisis in France, Germany, Greece, Italy, Portugal and Spain. We measure banks’ marginal cost by their rate on new deposits, contrary to the literature that focuses on money market rates. This allows us to account for banks’ risks. We focus on the interest rate on new short-term loans granted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 60 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…money market funds or floating rate notes) may not foresee the possibility of payments from the system as it prevents banks with high reliance on retail deposits from fully adjusting their funding costs. The literature on interest rate pass-through for the euro area finds evidence of imperfect pass-through onto loan rates (see Berke et al, 2013;Hristov et al, 2014;Gambacorta et al, 2015;Avouyi-Dovi et al, 2017;Horvath et al, 2018). The resulting squeeze in profit margins may impair the standard interest rate channel because high deposit banks might start raising loan rates instead of lowering them in response to a policy easing to protect their profit margins.…”
Section: The Transmission Mechanism Of Monetary Policy Under Nirpmentioning
confidence: 99%
“…money market funds or floating rate notes) may not foresee the possibility of payments from the system as it prevents banks with high reliance on retail deposits from fully adjusting their funding costs. The literature on interest rate pass-through for the euro area finds evidence of imperfect pass-through onto loan rates (see Berke et al, 2013;Hristov et al, 2014;Gambacorta et al, 2015;Avouyi-Dovi et al, 2017;Horvath et al, 2018). The resulting squeeze in profit margins may impair the standard interest rate channel because high deposit banks might start raising loan rates instead of lowering them in response to a policy easing to protect their profit margins.…”
Section: The Transmission Mechanism Of Monetary Policy Under Nirpmentioning
confidence: 99%
“…More recently, research has focused on the post-financial crisis era, showing increased fragmentation across countries (Ciccarelli et al, 2014;Aristei and Gallo, 2014) and less completeness of pass-through (Hristov et al, 2014). This divergence has been explained by higher funding costs (Illes et al, 2015), funding uncertainty (Ritz and Walther, 2015) and the changing marginal cost of raising deposits (Avouyi-Dovi et al, 2017). The use of micro data on banks balance sheets has grown to help understand the factors underlying these changes.…”
Section: Introductionmentioning
confidence: 99%
“…They found that correlation between policy rates and bank lending rates were reduced during crises due to increased risks. Similarly, Avouyi-Dovi et al (2017) found that interest rate pass-through was weakened during most financial crises in the Eurozone countries. Recently Horvath et al (2018) estimated the interest rate pass-through for the Eurozone throughout 2008-2016 using the heterogeneous panel technique PMG.…”
Section: Literature Reviewmentioning
confidence: 89%